Desenvolvimento sustentável e pobreza multidimensional na Amazônia Legal - Silva, Camila Parizotto da (2025)
A complex interaction between socioeconomic inequality and environmental degradation characterizes the relationship between poverty and the environment in the Legal Amazon. This study aims to analyze the relationship between multidimensional poverty and the environment in the Legal Amazon from 2012 to 2022, investigating how deforestation intensifies multidimensional poverty in the region. The methodology is based on the Alkire-Foster method to measure multidimensional poverty, considering the following dimensions: income (per capita income, Gini index, and poverty rate), education (average years of schooling and illiteracy rate), health (access to water, sanitation, and life expectancy), and environmental vulnerability (deforestation and emissions). Secondary data were collected from IPEADATA, INPE, IBGE, and SEEG and analyzed using statistical and geospatial techniques with QGIS, Microsoft Excel, and Python. The results indicate that poverty (H) increased from 77.78% in 2012 to 88.89% in 2022. However, poverty intensity (A) declined over the period, as the share of deprived indicators among the poor dropped from 69.05% in 2012 to 56.25% in 2022. The proportion of the population classified as multidimensionally poor (M0) decreased from 53.70% in 2012 to 50% in 2022. The education dimension significantly improved, reducing its contribution to the poverty index from 29.94% in 2012 to 9.34% in 2022. The income dimension exhibited minor fluctuations, while the health dimension increased its contribution, reflecting worsening access to essential healthcare services. The environmental vulnerability dimension rose from 19.91% in 2012 to 38.66% in 2022, indicating that environmental factors increasingly contribute to multidimensional poverty, exacerbating deprivation and affecting the quality of life of the most vulnerable populations. The states with the highest levels of deforestation also exhibited the most severe deprivation across all dimensions. Additionally, the findings suggest that if environmental indicators (deforestation and emissions) met sustainable development standards, M0 would have decreased from 54% to 32.72% in 2012 and from 51% to 29.78% in 2022. The study highlights the interconnection between poverty and the environment, emphasizing the need for public policies aligned with the Sustainable Development Goals (SDGs), particularly SDG 1 (no poverty), SDG 2 (zero hunger and sustainable agriculture), SDG 3 (good health and well-being), SDG 4 (quality education), SDG 6 (clean water and sanitation), SDG 8 (decent work and economic growth), SDG 10 (reduced inequalities), SDG 13 (climate action), and SDG 15 (life on land). The study concludes that integrated public policies, combining environmental conservation and social development, are essential to reversing this scenario and promoting a sustainable economic growth model in the region.